The Pengaruh media Big book terhadap hasil belajar siswa mata pelajaran PAI kelas IV SD - Kurniati Nia; Lailatul Muslimah; Anisa Fitriani (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Abstrak: This research investigates the impact of Big Book media on the learning outcomes of fourth-grade students in Islamic Religious Education at SD Negeri 30 Sungai Kosak. The study aimed to identify differences in students’ learning outcomes before and after the application of Big Book media in IRE instruction. A quantitative approach was employed using a pre-experimental method with a one-group pretest–posttest design. The participants consisted of 17 fourth-grade students, all of whom were included as the research sample through a saturated sampling technique. Data were gathered using multiple-choice tests administered as a pretest and a posttest. The data were analyzed using descriptive and inferential statistical techniques, with the Wilcoxon Signed Rank Test applied due to the data not meeting normality assumptions. The findings revealed that the mean pretest score of 62.06 increased to 92.35 in the posttest. The Wilcoxon test results showed a significance value (p-value) of less than 0.001, indicating a statistically significant difference between learning outcomes before and after the implementation of Big Book media. Additionally, the effect size analysis demonstrated a very strong effect. Thus, it can be concluded that the use of Big Book media is highly effective and significantly enhances students’ learning outcomes in Islamic Religious Education for fourth-grade students at SD Negeri 30 Sungai Kosak.